Problems of Modern Approaches in Teaching Foreign Languages at Technical Universities - Kushakov Yu.X (Genius Publishing Group, 2022)
In this article, modern approach problems in teaching foreign languages, are revealed, as they have a special specificity that a foreign language teacher cannot ignore during the lessons. According to the author modern approaches are of great importance in the organization of the learning process. The author divides these approaches into several types as student –centered approach, interactive approach, an approach of development education, game learning, problematic approach, communicative approach, project method and the competence-based approach. As the author considers all of these approaches have their own features and foreign language teachers should take into account when they conduct lessons. The author highlights the main problems in this sphere.
Keywords: An approach; modern approaches; communication; communicative